Novel immunohistochemical markers differentiate intrahepatic cholangiocarcinoma from benign bile duct lesions. Issue 7 (4th January 2016) - Bertram, Stefanie; Padden, Juliet; Kälsch, Julia; Ahrens, Maike; Pott, Leona; Canbay, Ali; Weber, Frank; Fingas, Christian; Hoffmann, Andreas C; Vietor, Antonie; Schlaak, Joerg F; Eisenacher, Martin; et al.
Abstract : Aims: The distinction between intrahepatic cholangiocarcinoma (ICC) and benign bile duct lesions can be challenging. Using our previously identified potential biomarkers for ICC, we examined whether these are useful for the differential diagnosis of ICC, bile duct adenoma and reactive bile duct proliferations in an immunohistochemical approach and identified a diagnostic marker panel including known biomarkers. Methods: Subjects included samples from 77 patients with ICC, 33 patients with bile duct adenoma and 47 patients with ductular reactions in liver cirrhosis. Our previously identified biomarkers (stress-induced phosphoprotein 1 (STIP1), SerpinH1, 14-3-3Sigma) were tested immunohistochemically following comparison with candidates from the literature (cluster of differentiation 56, heat shock protein (HSP)27, HSP70, B-cell-lymphoma2, p53, ki67). Results: The expression of SerpinH1 and 14-3-3Sigma was significantly higher in ICC than in bile duct adenomas and ductular reactions (p<0.05), whereas STIP1 expression was significantly higher (p<0.05) in ICC than in ductular reactions, but the difference to the bile duct adenoma group was not significant. A panel of the biomarker SerpinH1, 14-3-3Sigma and ki67 (≥2 marker positive) showed a high diagnostic accuracy (sensitivity 87.8%, specificity 95.9%, accuracy 91.8%) in the differential diagnosis of ICC versus non-malignant bile duct lesions. Conclusions: This suggests that 14-3-3Sigma and SerpinH1 may be useful in the differential diagnosis of malignant, benign and reactive bile duct lesions in addition to ki67 where a cut-off of >5% might be used for the distinction of malignant and non-malignant lesions.